Rancangan Video Pembelajaran Penatalaksanaan Kegawatdaruratan Psikiatri Metode Restrain Safety - Indah Mukarromah (Universitas Pesantren Tinggi Darul Ulum, 2017)
Abstract Psychiatric emergencies often occur in both the service and the community. Need for socialization about the management of the patient, one of them is by way of restrain. The purpose of making this learning video is because there are still many people who do actions pasung on people with mental disorders so that this media helps readers to disseminate safe way of restrain. The methods used include using hardware and software tools. The hardware device is the Mini 210 Hewlett-Packard (Hp) Notebook, whereas to combine the appropriate software files of Intel Atom (TM) processor CPU N550 @1.50 GHz 1.50 GHz Windows 7 Starter 2009; Camtasia 8.4 (TM) TechSmith Corporation version 8.4.0.1699; CyberLink YouCam Corporation version 4.0.0.8.2.0; Microsoft Office Professional Plus Power Point 2010 version 14.0.4763.100 with the title of restrain. Also using some background music and videos that are downloaded at youtube. Upload using social media facebook Indah Mukarromah/Hakuna Matata. Assessment using 3 validation ways that is expert validation, testing, and publish. The results showed that 4 respondents from 10 respondents gave feedback, expertly validated and the experiments showed an average of 80. However, publish validation required additional improvements in the image media in the presentation slides, less maximal narrator volume, and the addition of effects-related material Side use of restrain. Making audio-visual learning media needs to be made manuscript so that there is equality of perception between designer and user. Keywords: Learning Video, Management of Psychiatric Emergency, Restraint Safety